PENGARUH ONLINE CUSTOMER REVIEW DAN PRODUCT KNOWLEDGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK IMPLORA MELALUI SHOPEE PADA MASYARAKAT DI KOTA SURABAYA - Hasanah, Nadiyatul; Maduwinarti, Ayun; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
Technology and information have progressed far from previous years, and the existence of the internet has a direct impact on people’s daily lives, one of which is in the field of marketing. Competition between businesses in the marketing world, especially in the field of beauty and skin health is growing rapidly. The purpose of this study is to determine and analyze the influence of Online Customer Reviews and Product Knowledge on Purchasing Decisions. This research method uses Quantitative research methods with an associate type of research. The population in this study is people who have bought Implora products through the Shopee Surabaya marketplace, with a sample of 100 respondents. This research data collection technique used e-questionnaire. The results and conclusions of this study show that Online Customer Review and Product Knowledge have a positive and significant effect both partially and simultaneously on the Purchase Decision of Implora Products in the people of Surabaya. The recommendation of this study is that companies need to pay attention to Perceived Usefulnes on the Shopee Surabaya marketplace by highlighting the benefit items of Implora products continuously.